2007
DOI: 10.1111/j.1365-2044.2007.05101.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from neuromuscular blockade: a survey of practice*

Abstract: Summary At present in the UK there is no consensus regarding the parameters anaesthetists use to indicate adequacy of reversal from neuromuscular blockade. In an attempt to determine current practice, we carried out a survey covering 12 anaesthetic departments throughout the UK. Individuals were asked to give details regarding their usage of available monitors or, alternatively, to list those clinical parameters which they felt offered the best guidance as to the adequacy of recovery from neuromuscular blockad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 16 publications
1
67
0
9
Order By: Relevance
“…A wrong judgement of recovery based on clinical assessment and early transfer to recovery room may lead to respiratory failure due to weakness in respiratory muscles induced by an insufficient reversal of neuromuscular block. It is suggested that postoperative hypoxia is closely related with residual neuromuscular block (8), patients could raise their heads for 3 seconds, open their eyes, stick their tongues out even when their TOF values are 60% nevertheless their vital capacity remains low (9). Surveys show that clinicians rely on clinical assessment for detection of residual neuromuscular block (10).…”
Section: Discussionmentioning
confidence: 99%
“…A wrong judgement of recovery based on clinical assessment and early transfer to recovery room may lead to respiratory failure due to weakness in respiratory muscles induced by an insufficient reversal of neuromuscular block. It is suggested that postoperative hypoxia is closely related with residual neuromuscular block (8), patients could raise their heads for 3 seconds, open their eyes, stick their tongues out even when their TOF values are 60% nevertheless their vital capacity remains low (9). Surveys show that clinicians rely on clinical assessment for detection of residual neuromuscular block (10).…”
Section: Discussionmentioning
confidence: 99%
“…En una encuesta realizada en Reino Unido se puso de manifiesto que sólo el 2.4% de los participantes monitorizaban siempre el BNM, y el 62% no lo hacía nunca 35 . El único método fiable para la monitorización de la función neuromuscular es la estimulación de un nervio periférico accesible y la medición de la respuesta evocada del músculo esquelético que inerva.…”
Section: Monitorización Neuromuscularunclassified
“…Además muchos tests (elevar la cabeza, apretar la mano) no son específicos de la musculatura respiratoria, y de su correcta realización no podemos inferir una adecuada función respiratoria. A pesar de ello, la mayoría de los anestesiólogos toman como referencia los signos clínicos y los test para descartar BNMR antes de extubar al paciente, y el test que se realiza con más frecuencia es el de mantener la cabeza erguida durante 5 segundos 35 , aunque pacientes recién operados 85 son capaces de elevar 5 segundos la cabeza con ratios del TOF < 0.5. Otros múltiples estudios han mostrado que con la presencia de diversos grados de parálisis residual los pacientes realizan correctamente los tests clínicos y que todos los tests presentan una baja sensibilidad (11-14%) para detectar valores del TOF-ratio < 0.9 2,86 , siendo la valoración de la fuerza del masetero (p.ej.…”
Section: Bloqueo Neuromuscular Residual (Bnmr)unclassified
See 1 more Smart Citation
“…9,27 After calibration of the device, the ulnar nerve was stimulated supramaximally N euromuscular blocking drugs (NBDs) are commonly used in anesthesia and to treat critically ill patients in intensive care units (ICUs), 1,2 but few clinicians use neuromuscular transmission monitoring. [3][4][5] In the United Kingdom, 31% of critically ill children are likely to receive NBDs, but the depth of the blockade is routinely assessed in only 16% of patients. 2 Results of a recent survey 4 indicated that only 22% of Canadian ICUs use standardized protocols for NBD application and that 16% of all Canadian intensive care providers do not use neuromuscular transmission monitoring at all.…”
Section: Methodsmentioning
confidence: 99%